2021
DOI: 10.1177/00033197211012129
|View full text |Cite
|
Sign up to set email alerts
|

The Atherogenic Index of Plasma: A Powerful and Reliable Predictor for Coronary Artery Disease in Patients With Type 2 Diabetes

Abstract: We evaluated the predictive power of the atherogenic index of plasma (AIP) for coronary artery disease (CAD) in patients with type 2 diabetes mellitus (T2DM). A total of 3278 patients who underwent coronary angiography were consecutively enrolled, including 2052 patients with CAD and 1226 patients with T2DM but without CAD. Patients in the CAD group had higher levels of triglyceride (TG), total cholesterol, low-density lipoprotein cholesterol, AIP and a lower level of high-density lipoprotein cholesterol (HDL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…A higher AIP level was also associated with an increasingly atherogenic lipid phenotype and cholesterol esterification rete 8,9) . Moreover, our present study and prior studies suggested AIP was relevant to various cardiometabolic risk factors [10][11][12] .…”
Section: Association Of Aip With the Risk Of Des-isr In Different Subgroupssupporting
confidence: 79%
See 4 more Smart Citations
“…A higher AIP level was also associated with an increasingly atherogenic lipid phenotype and cholesterol esterification rete 8,9) . Moreover, our present study and prior studies suggested AIP was relevant to various cardiometabolic risk factors [10][11][12] .…”
Section: Association Of Aip With the Risk Of Des-isr In Different Subgroupssupporting
confidence: 79%
“…Although the potential mechanisms underlying AIP and DES-ISR were unknown at present, several possible explanations were listed according to previous studies. First, this study and prior studies all suggested AIP correlates positively with various metabolic disorders such as insulin resistance, DM, hyperglycemia, and hyperuricemia 10,11) , all of which were well-established risk factors for ISR [29][30][31] . Second, remnant-lipoprotein cholesterol, as a risk factor for the occurrence and development of ISR 32,33) , is usually increased with increasing AIP levels 8,10) .…”
Section: Declaration Ethics Approval and Consent To Participatementioning
confidence: 52%
See 3 more Smart Citations